Shaping the Hospital of the Future: Improve the User Experience in the Public Healthcare Sector Through Service Design Education - Giambattista, Angela; Di Lucchio, Loredana; Zolotova, Mariia (Design Management Journal)
The Public Healthcare Sector is experiencing a profound crisis due to socio‐dynamic changes (Parameswaran and Raijmakers, 2010) difficult to manage, such as demographic aging and population growth. Furthermore, if we consider the new alternative approaches in disease management and the growing participation of patients in healthcare decision making (Vahdat et al., 2014), deep considerations and paradigmatic shifts in the way healthcare professionals design, produce and use the medical products are needed. The growing interest in the potential of Design approaches, from which to draw consolidated models of thought and creative and divergent practices (Chamberlain, 2015) to respond to fundamental challenges for the health of our society, has recently expanded from the dimension of products and services. This represents an unmissable opportunity for the Design Discipline to switch from a Product‐Centered model to a Human‐Centered model where the user is placed in the center of the process and the product expands into product/service with a systemic perspective. The introduction of Service Design in medical settings requires a multilevel approach that analyzes the complexity of the system, in which the nature of the problems intersects with economic and social dynamics too (Di Lucchio and Giambattista, 2017). From this point of view, the methodologies of Service Design offer conceptual models that help to focus the design action on the User Experience, considering all the characteristics of the service in a structured way and openly thinking about the individual components without losing the holistic view. According to this new perspective and given the growing relevance of services in the contemporary economy, in the corporate strategies and in the public sector, the academic approach to Service Design and the Service Design Education in the context of Healthcare need to be revised through a better definition of design competencies (Morelli and Götzen, 2017). In the light of these considerations, this paper describes the didactic experience held within an International Master of Science in Product Design at Sapienza University of Rome, where the students have experimented the methods of the Service Design (Stickdorn et al., 2011) to respond to the problem of designing the User Experience (Norman, 2004) in a Public Healthcare Context. The aim was to transfer to the students the skills useful for achieving a Service and Social Innovation (Manzini, 2015) in the